ANALYSIS OF NEEDS FOR A DIGITAL AUTOMATED SHORT ESSAY SCORING (ASES) BASED ASSESSMENT MODEL IN ENGLISH LEARNING IN VOCATIONAL SECONDARY SCHOOLS - Susilawati, Evi; Khaira, Imamul; Rambe, Isnaini Halimah; Sembiring, Metrilitna Br; Siregar, Wildawani; Octariani, Dhia (Universitas Islam Sumatera Utara (UISU), 2023)
The aim of this research is to look at the needs analysis of the digital-based assessment model Automated Short Essay Scoring (ASES) in English language learning in Vocational High Schools. This research is a research and development (RD) research carried out in the Computer Network Technology Department at SMK Negeri 1 Percut Sei Tuan. This research is included in mixed methods research with the assessment development model used, namely the Borg and Gall model which consists of ten stages,: needs analysis, development plan, initial product development, initial test or one-on-one test, initial product revision, field test, product revision, field implementation test (operational test), revising the final product, and implementation in the field. This research focuses on the first step of all the steps in developing the Borg and Gall model above, namely needs analysis activities. The results of this research show that the implementation of digital assessment models needs to be carried out in English language learning. The use of ASES digital-based assessment media is an urgent need for assessment to be implemented to take into account the knowledge, skills, dispositions and attitudes needed to equip students to keep up with the increasingly changing digital world. Furthermore, identification of the development of the ASES digital-based assessment model in English language learning at Vocational High Schools was carried out by conducting FGDs with teachers and students of SMK Negeri 1 Percut Sei Tuan resulting in an agreement that in learning English students need to be equipped with digital skills.